2017
DOI: 10.4314/tjpr.v16i9.17
|View full text |Cite
|
Sign up to set email alerts
|

Curative role of lactulose, L-carnitine, alpha-lipoic acid and combination of L-carnitine and alpha-lipoic acid in a rat model of acute hepatic encephalopathy: Biochemical observations

Abstract: Purpose: To determine whether a combination L-carnitine and α-lipoic acid (ALA) can alleviate the toxic effects of thioacetamide (TAA) via their potent antioxidant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…L-carnitine, taurine, carnosine, N-acetyl cysteine, and α-lipoic acid supplementation have been tested as hepatic/neuroprotective agents in animal models or clinical studies. [6][7][8][9][10][11][12][13][14] Citicoline is a principal intermediate in the biosynthesis pathway of phosphatidylcholine. 15 Several investigations revealed that citicoline acts as a neurovascular protecting agent.…”
Section: Introductionmentioning
confidence: 99%
“…L-carnitine, taurine, carnosine, N-acetyl cysteine, and α-lipoic acid supplementation have been tested as hepatic/neuroprotective agents in animal models or clinical studies. [6][7][8][9][10][11][12][13][14] Citicoline is a principal intermediate in the biosynthesis pathway of phosphatidylcholine. 15 Several investigations revealed that citicoline acts as a neurovascular protecting agent.…”
Section: Introductionmentioning
confidence: 99%